Factors influencing secondary school students’ nutrition, mindfulness, and academic performance in Nan Province, Thailand - Ei Zar Lwin; Dorn Watthanakulpanich; Athit Phetrak; Ngamphol Soonthornworasiri; Pattaneeya Prangthip (PLoS ONE, 2025)
Academic performance is crucial for future educational endeavors of students. However, there has been a concerning decline over time. This study aimed to investigate the association between nutritional status, environmental factors, mindfulness, and academic performance among students at Bo Kluea School in Nan province, Thailand. A cross-sectional study was conducted involving 350 students in grades 8–11 using questionnaires, measurements, and academic records. Results showed that female students performed significantly better academically compared to males(71.9% vs 56.4% achieving good grades; compared to p < 0.001, OR = 3.583, 95%CI = 1.663–7.719). Age, junk food consumption, BMI, and mindfulness were identified as factors influencing academic performance. Students aged 16–18 years were 2.224 times more likely to achieve good academic performance compared to younger students (p = 0.015, OR = 2.224, 95%CI = 1.164–4.247). Significant associations were found between gender, age, waist circumference, mindfulness, and nutritional status. Female students and those with normal waist circumference or good mindfulness were more likely to have a normal BMI (p = 0.019, OR = 1.794, 95%CI = 1.101–2.922). Positive attitudes towards nutrition were associated with better academic performance (60.1% achieving good grades;p = 0.044, AOR = 1.543, 95%CI = 1.010–2.356). This study highlights the interconnectedness of these factors and their importance in in improving academic results. Further research is need to confirm these findings and overcome study limitations.